Climate data empathy. (19th November 2018) - Brönnimann, Stefan; Wintzer, Jeannine
Abstract : In the era of climate services, which provide globally complete data products in a ready‐to‐use form, the context of climate data is in danger of being neglected or forgotten. However, the historical and present‐day context imprinted on this climate data is important in its own right. The data depend on political, economic and technological factors, as we show with a range of data coverage maps. We term awareness of and sensitivity to this context‐dependence "climate data empathy, " and argue that context should be seen as a source of information to be communicated along with the data. Such context not only provides additional information about the data products, but may help in designing communication strategies and contribute more generally to raising awareness of the contingency of environmental data. Decision making should thus make use of both climate data and its context. This article is categorized under: Climate, History, Society, Culture > Technological Aspects and Ideas Abstract : Climate measurements also measure the needs of the powerful. Coverage from 1947 shows nation states, trade, and a colonial world.